(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: 1) Determine the waiting time for medical examination of outpatients at the Examination Department, Ky Anh General Hospital, Ha Tinh in 2024. 2) Analyze some factors affecting the waiting time for medical examination of outpatients at the Examination Department, Ky Anh General Hospital, Ha Tinh, in 2024. Research method: Cross-sectional study combining quantitative and qualitative, conducted on 220 patients and hospital medical staff. Descriptive statistics and analysis methods were applied together with the T-test, Anova test, and the statistical significance threshold was p<0.05. Main findings: The average TGC of patients at the Examination Department was 110.7 ± 61.6 minutes; In all stages at the Examination Department, the longest waiting time for patients is for test results (67.8 ± 32.1 minutes), the shortest waiting time is for ultrasound results (6.1 ± 1.9 minutes). There is a statistically significant difference in the TGC of patients in the following characteristics: number of CLS performed, examination form by specialty, time, date of registration for examination, and age group (p<0.05). Patients coming for examination in the morning have a longer TGC; the age of patients is related to reading, understanding, and complying with regulations/procedures; the hospital lacks instructions in the ultrasound room; the facilities are cramped, lacking chairs; the arrangement of the examination room is easy to move; there is a lack of X-ray machines; the hospital still lacks regular doctors in the Examination Department, and lacks staff to dispense medicine. Conclusions: The waiting time for patients is still high, concentrated in the morning, and the hospital still lacks human resources and medical equipment.